Understanding of Early Adolescence Sexuality in the Digital Era - Mierrina; Hamidah, Ni’matul (International Conference on Sustainable Health Promotion, 2023)
The digital era is an era or era that experiences conditions of progress in the all-gigital field of life. The development of the digital era is advancing rapidly and humans cannot stop it, in which there are both benefits and negative impacts.individuals of all ages cannot be seprated from digital devices, including teenagers, especially early adolescents. Early adolescence, which is between 12 and 15 years old, is often considered a negative period, they have a desire to try new things. One of the topics that teenagers are interested in is sexuality. The digital era allows access to global information that is easier and wider, enabling adolescentsto fulfill their curiosity about sexuality by accessing it thrught various digital platforms and social media. This study aims to provide an overview of the understanding of early adolescent sexuality in the digital era. It is research with quantitative methods, using a questionnaire as a data mining tool.